Shooting dynamics in archery: A multidimensional analysis from drawing to releasing in male archers - Tinazci, C. (Procedia Engineering, 2011)
The purpose of this study is to investigate the relationships between physiological and mechanical dynamics during arrow releasing in archery with the quality of the arrow shot. Four elite male archers were involved in this study. Mechanical clicker reaction time (MCRT), Integrated Electromygraphic % (IEMG %) activity of hand flexor and extensor, deltoid and trapezius were recorded at a sampling frequency of 600 Hz. Aiming behaviours, aiming time, total drawing time (TDT) and full drawing time (FDT) were calculated by the first act in trapezius. Postural sway, aiming sway and body weight shifts, changes in the posture of archers toward sideways (DX) and front-back (DY), decrease in the body weight (DBW) on legs were recorded at the same sampling rate using force plates for every arrow of archers. All the measurement methods were synchronized with each other and referenced to the clicker fall. Subjects completed 30 arrows on an 18m range constructed indoors. Statistical analysis was conducted using SPSS 12.0. It has been found that performance of male archers varies according to flexor muscle one second prior to clicker falls and that the performance increases when the muscular activity of flexor and deltoid muscles decreases. It has been stated that archers have better shots as the posture sways towards right-left within the period of holding the bow tight and as the drawing time decreases. In conclusion, archers MCRT is shorter for high performance. As muscle activity decreases, performance increases. Aiming sways on the target towards right-left, up and down and postural sways during releasing towards sideways and anterio-posterior affect performance. Drawing time may change with performance and which is affected by shift in the body weight especially after releasing.